Pengaruh Pengungkapan Emisi Karbon Terhadap Nilai Perusahaan Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia - Istiqomah, Istiqomah; Anshari, Rahman; Jamal, Sri Wahyuni (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The goal of this study is to look at how different sectors' stock prices changed when companies disclosed their carbon emissions on the Indonesia Stock Exchange from 2018 to 2022. For this study, 154 research samples were obtained from 42 different organisations using a purposive sampling technique. An independent variable used in this study is the carbon emission disclosure (CED) list, which is a product of the carbon disclosure project (CDP). This study just makes use of profitability as a control variable. The data is analysed using a multiple linear regression model. According to these findings, a company's value drops sharply if its carbon emissions are made public. According to this research, businesses still haven't worked out how to tell the world about their carbon footprints, which means they're missing out on opportunities to win over stakeholders and consumers. There may not have been adequate communication to address the problem, and managers and stakeholders may not understand the significance of this revelation.